2021
DOI: 10.2147/ijn.s321984
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic Iron Oxide Nanoparticles: Cytotoxicity, Metabolism, and Cellular Behavior in Biomedicine Applications

Abstract: Superparamagnetic iron oxide nanoparticles (SPIONs) have been widely investigated and applied in the field of biomedicine due to their excellent superparamagnetic properties and reliable traceability. However, with the optimization of core composition, shell types and transfection agents, the cytotoxicity and metabolism of different SPIONs have great differences, and the labeled cells also show different cellular behaviors. Therefore, a holistic review of the construction and application of SPIONs is desired. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 114 publications
(140 reference statements)
2
45
0
Order By: Relevance
“…In addition, the specific features of the various formulations also have to be carefully considered, as the size and surface functionalization of SPIONs can strikingly affect the toxicity. Therefore, studies focusing on the biological distribution and metabolic pathways of the MNPs in cells or bodies will lead the future evolution of research in this field [61].…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the specific features of the various formulations also have to be carefully considered, as the size and surface functionalization of SPIONs can strikingly affect the toxicity. Therefore, studies focusing on the biological distribution and metabolic pathways of the MNPs in cells or bodies will lead the future evolution of research in this field [61].…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%
“…Iron oxide-based MCs include: SPIOs (superparamagnetic iron oxide nanoparticles); USPIOs (ultrasmall superparamagnetic iron oxide nanoparticles); and MPIOs (microparticles of iron oxide). Although MCs are typically used to accelerate the transverse relaxation, some IONPs can also serve as T 1 contrast agents, primarily reducing the longitudinal relaxation time [61,[342][343][344]. The most commonly used MCs in the clinics are the USPIOs, which have typical diameters ranging from 20 to 50 nm and are characterized by a long circulation half-life.…”
Section: Imaging Techniques To Visualize Mcsmentioning
confidence: 99%
“…The low toxicity of SPIONs to healthy/normal cells offers a critical advantage, compared to other inorganic nanoparticles. SPIONs are also able to cross the nuclear membrane [ 127 ] and generate ROS [ 128 , 129 ]. In a study by Afrasiabi et al [ 130 ], SPIONs were shown to generate more ROS in oral squamous cell carcinoma (OSCC) mitochondria than in normal cell mitochondria.…”
Section: Mitochondria-targeting Nanoparticles For Advancing Cancer Th...mentioning
confidence: 99%
“…The clinical use of HIFU is increasing, but damage to the skin and adjacent healthy tissues cannot be ignored. Superparamagnetic iron oxide nanoparticles (SPIONs) have great prospects in the biomedical field, especially as ultrasound absorbers, owing to their reliable sources and excellent superparamagnetic properties ( Wei et al, 2021 ). Devarakonda et al (as cited in Sun et al, 2014 ) improved the thermal ablation effect of tumors by combining the advantages of SPIONs and polymers to construct PLGA-coated Fe 3 O 4 microcapsules to enable energy deposition and enhance the absorption of ultrasonic waves.…”
Section: Non-invasive Thermal Ablation Assisted By Transition-metal B...mentioning
confidence: 99%